HLA typing using next-generation sequencing for Chinese juvenile- and adult-onset myasthenia gravis patients. (January 2019) - Feng, Xuelin; Li, Wenhui; Song, Jie; Liu, Xiaoni; Gu, Yuehua; Yan, Chong; Wu, Hui; Xi, Jianying; Zhou, Shuizhen; Zhao, Chongbo
Graphical abstract: Highlights: Next-generation sequencing is a precise gene sequencing technique in HLA typing. The HLA background is different between Chinese juvenile- and adult-onset myasthenia gravis patients. JOMG represents a crucial MG subgroup in China. Abstract: To compare HLA typing between juvenile- and adult-onset myasthenia gravis (MG), we enrolled 101 children (age ≤12 years) and 168 adults (age ≥20 years) with MG. We excluded patients with histories of thymoma, thyroid disease, or other autoimmune disease. We selected 41 seronegative juvenile-onset patients with ocular symptoms only, and 41 seropositive adult-onset patients with generalized symptoms. We used next-generation sequencing for typing and analysis of HLA genes (Loci: A, B, C, DPA1, DPB1, DQA1, DQB1 and DRB1). Haplotypes HLA-A∗02:07:01-B∗46:01:01-C∗01:02:01-DQA1∗01:01:01-DQB1∗03:03:02-DRB1∗09:01:02, HLA-A∗11:01:01, HLA-A∗24:02:01, and HLA-DPA1∗02:02:02 were found to be related to juvenile-onset MG and HLA-A∗01:01:01, HLA-A∗02:03:01, HLA-C∗03:04:01, and HLA-DQB1∗06:02:01 to adult-onset MG. Therefore, our findings suggested that HLA typing might determine the heterogeneity between AChR-Ab negative juvenile-onset and AChR-Ab positive adult-onset Chinese MG patients.